Cure kinetics, glass transition advancement and chemo-rheological modelling of an epoxy vitrimer based on disulphide metathesis - Anagwu, Festus Ifeanyi; Skordos, Alexandros A. (Elsevier, 2023)
This study develops cure and chemo-rheological models for a vitrimeric system appropriate for use as matrix in continuous fibre composites based on a disulphide-endowed amine/epoxy formulation. The focus is on the processing conditions relevant to liquid composite moulding. Kinetics is investigated using Differential Scanning Calorimetry. An autocatalytic model is developed, simulating the reaction with an average reaction rate error of 5.2 % and degree of cure error of 3 %. The viscosity development is modelled at relatively low degrees of cure, focusing on the liquid moulding infusion window, yielding results with an average relative error of 4.8 %. The glass transition temperature advancement is represented by the Di Benedetto equation, whilst the topological transition temperature of the system is determined using stress relaxation experiments and found to be 149.5 °C. These results set the scene for the development of composites based on the matrix system investigated in this work.
Keywords: Cure kinetics; Vitrimers; Composites; Chemo-rheology; Glass transition; Topology transition